AYURVEDIC DIETARY CONCEPTS IN DIFFERENT AGE GROUP OF CHILDREN - Shamama Firdaus,; Sunil Topre,; Nitin Mane, (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda is a science of life, which mainly aims to promote and preserve the health of the individuals. In this techno and competitive era, life style and diet are major factors influencing the health of the individuals. Diet and dietary habits play important role in maintenance of health. Ayurveda, its main aim is to promote and preserve the health, strength and longevity of healthy person and to cure the disease. Ayurveda places special emphasis on Ahara and believes that healthy nutrition nourishes the Sharir, Mana, Atma. As Acharyas has described Ahara. Nidra, Brahmcharya are Tryoupsthambha (sub pillars) which support the body itself. Here Ahara has been placed first which shows that it is most important to maintain and sustain of life. Children are delicate and most sensitive and prone to the infectious diseases. They are miniature of adult. They are in Ajatvyajanawastha (developing stage). Psychologically they are innocent. Being in developmental phase, Ahara plays very important role in the life of children. So parents should be aware of dietetic components required by child in different age groups.